Investigation on nutritional compounds and toxic elements in dietary supplements from young green barley (Hordeum vulgare L.) - Anna Sadowska-Rociek; Magdalena Surma; Adam Florkiewicz (NFS Journal)
Background: Young green barley is rich in nutrients and bioactive substances and hence is used for dietary supplement production. However, polluted environment and the use of pesticides can lead to the contamination of raw plant material. Purpose of the study: 1) determination of the young barley ingredients considered beneficial to the body (antioxidant activity, total polyphenols, phenolic acids, sodium, potassium, magnesium, calcium, iron, manganese, zinc); 2) assessment of the potential risk to human health posed by contaminants (pesticides, polycyclic aromatic compounds (PAHs), arsenic, cadmium, mercury, lead). Materials: dietary supplements containing green barley in a form of tablets, powders and juices. Methods: Ultraviolet-visible (UV–Vis) spectrometry (determination of antioxidant activity and total polyphenols), atomic absorption spectrometry (AAS; used for element determination), liquid chromatography (phenolic acids, some pesticide analysis); gas chromatography coupled to mass spectrometry (GC–MS; pesticide and PAH determination). Main findings: the young barley powders were rich in macro- and microelements, particularly Fe and Mn, and could meet up to 20 % of the human requirements. However, they were also considerably contaminated with heavy metals and imidacloprid. The maximum levels established in European Union for examined substances were exceeded in the case of imidacloprid (6 samples of barley powders: P1, P2, P7-P10), PAH4 sum (one sample of barley powder - P10), and mercury (2 samples of barley powders: P6 and P12, 3 samples of tablets – T1, T2, T14). Calculated risk assessment also indicated that regular consumption of these dietary supplements could pose a significant health risk in case of arsenic. Conclusions: the research suggests that although young barley powders exhibit a substantial amount of macro and microelements, and additional bioactive ingredients they may also be a potential source of some harmful substances such as heavy metals or pesticide residues.